2021
DOI: 10.7716/aem.v10i3.1803
|View full text |Cite
|
Sign up to set email alerts
|

Exploring microwave absorption by non-periodic metasurfaces

Abstract: In recent years there has been a large body of work investigating periodic metasurface microwave absorbers. However, surprisingly few investigations have focused on the absorption performance of similar non-periodic designs. In this work, the electromagnetic response of a large area (310 mm x 310 mm) microwave absorber that lacks a global periodicity is experimentally studied. The top metallic layer of the ultra-thin (0.3 mm) absorber is structured with rectangular patches given by a procedurally generated non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, for both polarisations, there is a clear branching of the 10 GHz mode for angles greater than 20°. This is due to the onset of diffraction, which occurs in periodic structures when the size of the unit cell is greater than half the wavelength 22 . The red dotted lines show the predicted diffraction edges (from simple diffraction theory), which correspond to the frequencies above which the onset of diffracted orders results in additional radiative loss channels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for both polarisations, there is a clear branching of the 10 GHz mode for angles greater than 20°. This is due to the onset of diffraction, which occurs in periodic structures when the size of the unit cell is greater than half the wavelength 22 . The red dotted lines show the predicted diffraction edges (from simple diffraction theory), which correspond to the frequencies above which the onset of diffracted orders results in additional radiative loss channels.…”
Section: Resultsmentioning
confidence: 99%
“…The specular reflectivity was also measured as a function of elevation ( ) angle (with normal incidence defined as 0°) between 7.5° and 65° from normal (in 5° steps) for both TM and TE polarised radiation, using a Naval Research Laboratory (NRL) arch 22 , shown in Fig. 2 c. The NRL arch consists of two broadband microwave horn antennas, which can independently move around the arch’s circumference to allow full characterisation of the specular reflectivity of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…[19] The absorbing performance of metamaterials can be readily adjusted by tuning their structure parameters, which allows them to surpass the limitations of traditional absorbing materials. [20][21][22][23][24][25][26][27][28] Plenty of metadevices have been developed, such as tunable absorbers, [29] active microwave camouflage, [30] and reconfigurable cloaks. [31] However, processing high-frequency metamaterials including photolithography, electron beam lithography, nanoimprinting, and laser ablation is usually difficult, time-consuming, and costly.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great interest attracted by periodic extraordinary transmitting structures, only limited attention has been paid to aperiodic arrays, i.e., those with arbitrary or even random separations between scatterers (either apertures or metallizations) [20,21] given the difficulty of their modeling [22,23]. For practical applications, local periodicity is assumed, and only smooth variations of geometrical parameters are used to limit aperiodicity effects [24,25].…”
Section: Introductionmentioning
confidence: 99%